REVITALISASI PEMBERDAYAAN BUDAYA KARAKTER NUANSA RELIGIUSTIK DALAM MEMBENTUK PERILAKU PEKERTI SANTRI - Innani Kholidatul Jannah; Fathor Rozi (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2021)
Abstarct: This writing aims to present a religious planting in shaping santri-like behavior. In shaping the character behavior of students, cultivation is very necessary. This research uses a qualitative approach with a type of case study. The results showed that the existence of a religious activity structure at the pesantren, such as the tahajjut prayer, dhuha prayer, fardhu prayer in congregation, and many other activities. By getting used to these activities, it becomes a shield (medicine) for every santri in forming a santri-like behavior.